Structural Change of Apoferritin as the Effect of pH Change: DLS and SANS Study - Arum Patriati; Nadi Suparno; Grace Tjungirai Sulungbudi; Mujamilah Mujamilah; Edy Giri Rachman Putra (Universitas Gadjah Mada, 2020)
Apoferritin is a complex protein potential for drug delivery application. The advantage of apoferritin lies in its core-shell structure, its nano size, and its pH-sensitivity. This study was aimed to characterize the structure of apoferritin due to the pH alteration effect in a solution using dynamic light scattering (DLS) and small-angle neutron scattering (SANS). Both DLS and SANS can observe protein size in solution near its physiological condition. The results show that apoferritin possesses a core-shell structure with a diameter of around 12–13 nm at pH 7. The dissociation of apoferritin occurs at pH 1.9. The SANS data shows the apoferritin at pH 1.9 was dissociated into the smaller oligomer. The structure of this smaller oligomer has a different configuration than the configuration of apoferritin subunits at pH 7. It can cause the failure of reassembly of apoferritin if the apoferritin is neutralized back to pH 7 after dissociation from pH 1.9.